Survey of perceived influence of the conceptual design model of interactive television advertising towards impulse purchase tendency - Sarif, Siti Mahfuzah; Ahmad, Azizah; Shiratuddin, Norshuhada (2016)
With the proliferation of technology assisted shopping, there is growing evidence that impulse buying is an emerging phenomenon, which has been the focus of this study.Literatures indicate that studies related to impulse purchase for interactive television (iTV) advertising are highly scarce.It was found that most of the existing impulse purchase elements are mainly focusing on traditional retail store, website advertising, and traditional TV advertising, but not on iTV advertising.Due to that, through a systematic process, a design model for developing iTV advertising with influence towards impulse purchase tendency was developed and tested in this study. The design model is named as iTVAdIP and comprises of three main components; technology, impulse purchase components, and development process. This paper describes the survey, which measures the influence of iTVAdIP design model towards impulse purchase tendency.37 potential advertising designers were involved in the survey. The results indicate that the iTVAdIP is practical and workable in developing iTV advertisement that could influence consumer to buy the advertised product.